Preserving Regional Television History. The NBN Television Archive Project - Hardy, Ann (Unlocking Television Archives in the Digital Era. 16th Media Mutations International Conference, 2026)
This paper details a decade-long collaborative project between the University of Newcastle (Australia) Library and NBN Television to digitise the “Channel 3” television archive, the first regional commercial TV station in New South Wales, established in Newcastle in 1962. The project leverages the invaluable practice-based experience of former television staff who worked during the industry’s analogue era. Having already digitised the “at risk” magnetic tape news content from 1982 to 1995, the team is now focusing on digitizing the 16mm film formats. Beyond the audiovisual materials, the archive also includes paper records such as cue sheets, index cards, scripts, and memorabilia. The paper will also briefly discuss the Linius “Whizzard,” a video content discovery and playlist solution developed in partnership between the University Library and IT Services. This tool provides access to the previously difficult-to-search news content from 1982 to 1995, enabling users to search videos, identify key content, and create custom playlists. This pilot project offers unprecedented access to the social and cultural history of the Hunter region, empowering users to curate content for research or personal interest.